{Genital GVHD in Female Children and Adolescents: A Systematic Review of Case Reports and Case Series.} - Tsimeki, Maria; Tsimpidakis, Antonios; Roidi, Stella; Gregoriadis, Themos; Soldatou, Alexandra; Kitra, Vasiliki; Michala, Lina (Children (Basel, Switzerland), 2023)
Genital graft-versus-host disease (GVHD) after hematopoietic stem cell transplantation (HSCT) is an underdiagnosed manifestation of chronic GVHD. Few articles have been published in pediatric populations, and there are no established guidelines for the management of this condition in children. This study aims to provide a systematic literature review of the published studies and cases of genital (vulvovaginal) GVHD in girls and adolescents post HSCT, with a focus on the time of diagnosis and clinical manifestations. The authors searched for English-language articles published after 1990, which included full patient details. Thirty-two cases of female patients under 20 years of age were identified. The median time of diagnosis was 381 days (IQR: 226-730 days), and 83{%} of patients developed Grade 3 vulvovaginal GVHD. Based on these observations, an early pediatric gynecologic examination of these patients, soon within the first year after HSCT, could be suggested for early diagnosis, treatment initiation and prevention of long-term complications.